The Association Between Body Dissatisfaction and Social Media Addiction Among Teenagers in Indonesia - Paradini Sukma Candra; Muhammad Ghifari Rifansha; Ni Komang Sanca Dara Dahnita; Putu Cicilia Rarasati Kuta; Lale Justin Amelinda Elizar (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Body dissatisfaction and social media addiction are two psychological problems that are often experienced by teenagers. Body dissatisfaction is a psychological concept that refers to an individual's negative feelings towards his body. Several studies have shown that the higher level of body dissatisfaction, the higher the tendency of social media addiction in adolescents. Individuals tend to compare themselves with others through their appearance on social media, thereby reducing their appreciation of their own body shape and becoming more insecure. These conditions can affect a person's overall mental and physical health. This literature review aims to examine the relationship between body dissatisfaction and social media addiction among teenagers in Indonesia. This literature review was conducted using the keywords “body dissatisfaction AND social media addiction AND teenagers”. This article uses 28 articles that were used as references in its preparation. In conclusion, based on research conducted in various countries, including Indonesia, there is a significant relationship between body dissatisfaction and social media addiction among teenagers. Teenagers who are dissatisfied with their physical appearance tend to use social media more frequently, and excessive use of social media can increase the risk of both body dissatisfaction and social media addiction.